Empirical studies on director shareholdings of SGX-listed companies. - Chew, Kim Cheer. (2008)
This study examines the director shareholdings of 446 companies listed on the Singapore Exchange (SGX). Director shareholdings, studied with respect to board leadership structure and board composition, are analyzed in relation to firm performance. Further analysis by industry type and market capitalization enhances the understanding of the effect of director shareholdings on firm performance.